Vanishing act / : Mystery at the U.S. Open - Feinstein, John (Yearling, 2008)
Eighth-grade sports reporters Susan Carol and Stevie reunite at the U.S. Open tennis championships where they investigate the mysterious disappearance of a top Russian player.